Development of Anti-Aging Cream Containing Natural Active Ingredients of Virgin Coconut Oil - Priwitaningrum, Dwi Lestari; Situmorang, Sarah Melati Putri; Maha, Hetty Lendora; Sumaiyah; Hanum, T. Ismanelly (Talenta Publisher, 2022)
The process of premature aging is a physiological process that will occur in every living thing that is most visible on the skin. Recent studies proved that premature aging process can be prevented by using anti-aging cosmetics containing antioxidants. Natural origins of antioxidant are more desirable than synthetic one as they have more benefits and guaranteed safety. Virgin coconut oil (VCO) is well-known with its excellent antioxidant activity and abundance availability in Indonesia. Therefore it was interesting to develop anti-aging cream containing VCO as an active antioxidant ingredient. VCO-containing anti-aging cream was formulated using a base of white vaseline. Evaluation of anti-aging cream showed that the anti-aging cream had a semisolid consistency, white color, and lemon-like aroma. The anti-aging cream was homogeneous with a pH of 5.9-6.1, with an oil-in-water cream type, and stable during storage. While the hedonic test showed that as much as 40.0%; 42.90%; 45.70% liked the color, the smell, and the texture of the anti-aging cream, respectively. It was concluded that virgin coconut oil can be formulated into an anti-aging cream that stable during storage and having the preferred color, aroma and texture. It is potential to be developed as anti-aging cream with natural origin ingredients.